Peer Education Improve Knowledge and Attitude About Sexual Behavior in Adolescents: A Literature Review - Elisa Elisa; Salma Adilanisa; Dina Indrati; Muhamad Jauhar; Maksuk Maksuk (International Journal of Advanced Health Science and Technology, 2022)
Adolescents are included in the high-risk age group. Increased free sex behavior in adolescents has an impact on sexual and reproductive health problems. This phenomenon is supported by the increasing number of sexually transmitted diseases in adolescents. Several programs and policies have been adopted to improve adolescent reproductive health through coaching and counseling. Adolescents have confidence in their peers so peer education is an alternative intervention in increasing awareness of reproductive health. This study aims to comprehensively analyze research articles that discuss the effectiveness of peer education on knowledge and attitudes about sexual behavior in adolescents. The research design uses a literature review through the journal databases PubMed, Science Direct, and EBSCO. Researchers analyzed 18 research articles based on the inclusion criteria set, namely the time of publication in the 2015-2020 range, using English, being accessible for free, and teenage respondents. The exclusion criteria consisted of married adolescent respondents and adolescent sexual violence behavior. Keywords using peer education, knowledge, attitude, sexual behavior. Data analyzed using a table containing the author, year, method, sample, and research results. The results of the analysis of research articles show that peer education is a preventive and promotive effort in increasing knowledge and attitudes about sexual behavior in adolescents. The role of peers is an important component in this health education model. This model can be integrated and modified in adolescent reproductive health services in health care facilities.